Heuristic evaluation of the sport analysis application interface - Ihsan, Nurul; Okilanda, Ardo; Sepriadi, Sepriadi; Farell, Geovanne; Shapie, Mohamad Nizam Mohamed; Zakaria, Jaffry bin (Retos, 2024)
AbstractThis study applied Nielsen's heuristics to assess the user interface of the Sport Analysis Application. The purpose of this application aid students in evaluating their performance based on test results and adhering to training guidelines derived from the application's recommendations. The primary framework used in this investigation is Nielsen's heuristics, coupled with experiments to gauge the extent to which the application's user interface aligns with user preferences (user-friendly). The study targeted a population of students, with a sample size of 100 individuals. Analysis and discussion were conducted through the distribution of questionnaires to participants. The research findings revealed that the Visibility of System Status score reached 151. Overall, the study concludes that the developed Sport Analysis Application successfully achieves its primary objectives with a user-friendly interface.